Viewpoints and cognition: Soft focus and multisensory integration - Wachowicz, Fatima (2021)
Viewpoints training has been a tool for dance and drama improvisation and composition. It is theorized that Viewpoints develops the senses to respond quickly to surrounding stimuli, highlights attention, improves the sense of aliveness on stage, develops awareness and group dynamics. Concepts from cognitive psychology were used to understand the processes that can take place during the training. It is suggested that a type of " synesthesia" may occur and increase the interaction between the senses. A quasi experiment was applied to investigate the perceptual and cognitive processes involved. Results reveal a positive impact on group synchrony and cohesion.